Philosophical realism between nature and common sense. Part I - Caro, Mario De (Studia Ecologiae et Bioethicae, 2017)
Over the last three decades, the number of philosophers who would define themselves as realists has been steadily growing all over the world, both in the continental and in the analytic tradition. In the first part of the article, the terms of the contemporary discussion on realism and antirealism will be introduced. Then a specific family of views, which could be called „common sense realism”, will be presented and discussed, also considering its attitude towards science.